FATIGUE LIFE PREDICTION OF BOX GIRDER OF BRIDGE BASED ON EQUIVALENT CRACK APPROACH - LUO YouHong; WU Xiao; DING ZhengNan; FENG XiaoHua (Jixie qiangdu)
According to the characteristics of structure of the crane box girder and its complex stress condition,an equivalent crack approach based on fatigue test data is presented to estimate the fatigue life. The fatigue test data can be well in reflecting the effect of stress concentration on fatigue risk points. The stress concentration effects at the fatigue dangerous location can be approximately equivalent to having a crack in an unwelded plate. Using paris law calculate the equivalent crack propagation. By comparing estimation results with fatigue test results in the literature,the proposed method is effective and feasible to estimate the fatigue life under constant amplitude loading,but it needs to be further researched for estimation fatigue life under variable amplitude loading.